The Current Situation, Challenges, And Paths of High-Quality Development of Generative Ai Music from the Perspective of Rural Revitalization - Gao Y. (The Development of Modern Education in the Context of Pedagogical Competenciology, 2024)
this paper presents a comprehensive examination of the current state of generative AI music and the associated challenges that accompany its development. Through a detailed analysis of recent advancements, this paper also proposes potential strategies for achieving high-quality development in this emerging field. The examination focuses on three key areas: technical advancements, creative applications, and ethical considerations [13]. Nowadays, when technology is moving forward, it is obvious that they will penetrate into music. Currently, melodies written with the help of artificial intelligence are becoming more and more popular, and therefore the relevance of studying this problem is increasing, since it is not always clear whether the use of AI in the creation of musical works has a positive effect from the point of view of ethics. The purpose of this study is to characterize and determine the place of artificial intelligence in art, and especially in musical art. According to the results of the research in this article, we came to the conclusion that the use of AI in music can make the process of its creation faster and simpler, as well as more customer-oriented, but it is necessary to understand that there are limitations. For example, a machine can take away a person's job, which will lead to unemployment. The article suggests for practical significance the need to reform the existing legislation in the field of AI and establish clear boundaries of its validity.
Keywords: музыка; искусственный интеллект; artificial intelligence; music; этические проблемы; ethical issues